Relationship Between Intracerebral Hemorrhage Volume on CT Scan and Glasgow Coma Scale Score: A Systematic Review of Randomized Controlled Trials and Primary Studies - Novita Lusiana (International Medical Journal Corp. Ltd, 2026)
Introduction Intracerebral hemorrhage (ICH) constitutes approximately 10–15% of all strokes globally and remains one of the most devastating forms of acute cerebrovascular disease, with 30-day mortality rates exceeding 40%. The Glasgow Coma Scale (GCS) and hematoma volume measured via non-contrast CT scan are two of the most widely studied clinical and radiological parameters in the acute prognostication of ICH. Despite robust individual evidence, comprehensive systematic synthesis examining the direct quantitative relationship between ICH volume on CT and GCS score is lacking. This systematic review aims to consolidate existing evidence on this critical association to inform clinical decision-making, risk stratification, and therapeutic planning. Methods A systematic literature search was conducted from inception through June 2025, in accordance with PRISMA 2020 guidelines. Studies were included if they reported quantitative data on both ICH volume (measured by CT-based ABC/2 or planimetric method) and GCS score in adult patients with spontaneous supratentorial or infratentorial ICH. Results A total of 18 eligible studies comprising 8,247 patients were included. ICH volume was consistently and inversely correlated with GCS score across all included studies (r = -0.58 to -0.82; all p < 0.001). Patients with GCS 3–8 (severe depression) demonstrated hematoma volumes significantly greater than those with GCS 9–12 (moderate) or GCS 13–15 (mild-to-normal): mean difference of 28.4 mL (95% CI: 22.1–34.7 mL; p < 0.001). An ICH volume threshold of ≥30 mL independently predicted GCS ≤ 8 (OR 4.21; 95% CI 3.15–5.63; p < 0.001). Intraventricular hemorrhage extension, deep ICH location, and hematoma expansion further amplified the GCS-volume relationship. The ICH Score (which integrates both GCS and volume) demonstrated superior prognostic accuracy (AUC 0.86–0.91) compared to either parameter alone. Discussion The strong inverse relationship between ICH volume and GCS score reflects the direct effect of hematoma mass on intracranial pressure and cortical/subcortical functional depression. Location-specific volume thresholds modulate this relationship: deep-seated hemorrhages (thalamic, basal ganglia) produce greater neurological depression at smaller volumes compared to lobar hemorrhages. Serial neurological assessment using GCS at 6 hours post-admission adds incremental prognostic value beyond baseline imaging. Clinicians must avoid prognostic nihilism, as aggressive neurocritical care may significantly attenuate predicted mortality. Conclusion ICH volume on CT scan is a robust, independent predictor of GCS score and neurological outcome. A cut-off volume of ≥30 mL represents a clinically meaningful threshold associated with severe consciousness depression (GCS ≤ 8) and adverse outcomes. Integration of both GCS and ICH volume into composite scoring (e.g., ICH Score, max-ICH Score) maximizes prognostic accuracy. Future prospective multicenter studies and well-powered RCTs are warranted to validate volume-specific GCS cut-points across diverse populations.